57. DISEASE MODELS OF PATIENTS TREATED AT THE REHABILITATION DEPARTMENT - GENERAL CLINIC OF THE HANOI UNIVERSITY OF PUBLIC HEALTH FROM JULY 2022 TO JUNE 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the disease patterns of patients treated at the Rehabilitation Department - General Clinic of the Hanoi University of Public Health from July 2022 to June 2023; Research method: This was a cross sectional study, collecting retrospective information and analyzed disease patterns from 1386 patient records treated at the Rehabilitation Department - General Clinic, University of Public Health from July 2022 to June 2023;Results: The 2 most common disease chapters of patients treated at the rehabilitation room were chapter XIII Diseases of muscles, bones, joints and connective tissue accounting for 82.9% and chapter V Mental and behavioral disorders accounting for 10.9%. The 5 most common diseases were back pain (36.0%), neck pain (31.4%), other arthritis (11.9%), specific developmental disorders of speech and language (7.9%), sequelae of cerebrovascular disease (2.0%).Conclusion: The disease model at the Rehabilitation Department were mainly musculoskeletal diseases and developmental disorders in children. Of these, back pain and neck pain account for the highest rates at 36.0% and 31.4% of the total number of treatments.It is necessary to develop a plan to develop strengths in the two main disease chapters according to the disease model: musculoskeletal and behavioral mental disorders. In addition, it is also necessary to strengthen communication activities about medical examination and treatment services at the Rehabilitation Department as well as strengthen cooperation with other units to expand the disease areas at the Rehabilitation Department and train human resources for disease chapters with few or no patients to meet the comprehensive rehabilitation examination and treatment service according to the general trend of the rehabilitation specialty.
Keywords: disease pattern; rehabilitation